2019 novel coronavirus (2019-nCoV) outbreak: A new challenge. (June 2020) - Lupia, Tommaso; Scabini, Silvia; Mornese Pinna, Simone; Di Perri, Giovanni; De Rosa, Francesco Giuseppe; Corcione, Silvia
Highlights: In December 2019, a novel Betacoronavirus (2019-nCoV; SARS-CoV-2) was recognised and has rapidly spread across continents. 71 333 cases (17 February 2020) have been reported among 29 countries on the four main continents with mortality of ∼2%. Fever with respiratory symptoms (e.g. cough, dyspnoea) are the first signs of the disease (COVID-19). High rate of radiological and clinically suspicious pneumonia were reported in the reviewed cohorts of patients. Risk of bacterial superinfection and empirical antibiotic coverage must be considered. Abstract: Objectives: Following the public-health emergency of international concern (PHEIC) declared by the World Health Organization (WHO) on 30 January 2020 and the recent outbreak caused by 2019 novel coronavirus (2019-nCoV) [officially renamed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)] in China and 29 other countries, we aimed to summarise the clinical aspects of the novel Betacoronavirus disease (COVID-19) and its possible clinical presentations together with suggested therapeutic algorithms for patients who may require antimicrobial treatment. Methods: The currently available literature was reviewed for microbiologically confirmed infections by 2019-nCoV or COVID-19 at the time of writing (13 February 2020). A literature search was performed using the PubMed database and Cochrane Library. Search terms included 'novel coronavirus' or '2019-nCoV' or 'COVID-19'. Results: Published cases occurred mostly in males (age range, 8–92 years). Cardiovascular, digestive and endocrine system diseases were commonly reported, except previous chronic pulmonary diseases [e.g. chronic obstructive pulmonary disease (COPD), asthma, bronchiectasis] that were surprisingly underreported. Fever was present in all of the case series available, flanked by cough, dyspnoea, myalgia and fatigue. Multiple bilateral lobular and subsegmental areas of consolidation or bilateral ground-glass opacities were the main reported radiological features of 2019-nCoV infection, at least in the early phases of the disease. Conclusion: The new 2019-nCoV epidemic is mainly associated with respiratory disease and few extrapulmonary signs. However, there is a low rate of associated pre-existing respiratory co-morbidities.